Life expectancy in metastatic prostate cancer patients according to racial/ethnic groups. (15th May 2021) - Würnschimmel, Christoph; Wenzel, Mike; Collà Ruvolo, Claudia; Nocera, Luigi; Tian, Zhe; Saad, Fred; Briganti, Alberto; Shariat, Shahrokh F; Mirone, Vincenzo; Chun, Felix KH; Tilki, Derya; Graefen, Markus; et al.
Abstract : Objectives: To quantify the magnitude of differences between observed overall survival and respective, age‐adjusted Social Security Administration life tables‐derived life expectancy in Caucasian, African American, Hispanic/Latino and Asian metastatic prostate cancer patients. Furthermore, to test for differences in cancer‐specific mortality and other‐cause mortality according to race/ethnicity. Methods: We relied on the 2004–2006 Surveillance, Epidemiology and End Results database to identify Caucasian, African American, Hispanic/Latino and Asian metastatic prostate cancer patients. Social Security Administration life tables were used to compute 10‐year life expectancy for comparisons with observed overall survival. Poisson regression plots showed cancer‐specific mortality relative to other‐cause mortality for each race/ethnicity. Results: A total of 2574 (64.2%) patients were Caucasian, 753 (18.8%) were African American, 453 (11.3%) were Hispanic/Latino and 227 (5.7%) were Asian, respectively. The median age at diagnosis was 72 years in Caucasian patients, 68 years in African American patients, 70 years in Hispanic/Latino patients and 72 years in Asian patients. Observed overall survival rates were always lower compared with respective predicted life expectancy. The magnitude of the difference between observed overall survival and predicted life expectancy at 10 years was highest in African American patients (−52.2%), followed by Caucasian patients (−48.3%), Hispanic/Latino patients (−46.1%) and Asian patients (−37.4%). African American patients showed the highest cancer‐specific mortality rates (71.1%) and second‐highest other‐cause mortality rates (17.4% vs highest 18.4% in Caucasian patients), despite having the youngest age at diagnosis. Asian patients showed the lowest cancer‐specific mortality rates (65.5%, P < 0.0001) and lowest other‐cause mortality rates (13.3%, P = 0.04), despite having the oldest age at diagnosis. Conclusions: Despite having the youngest age at diagnosis, African American patients show the least favorable survival profile in metastatic prostate cancer. Conversely, Asian patients show the most favorable survival profile in metastatic prostate cancer, despite having the oldest age at diagnosis.